Advanced dementia: opinions of physicians and nurses about antibiotic therapy, artificial hydration and nutrition in patients with different life expectancies. Issue 3 (23rd March 2016) - Pengo, Valentina; Zurlo, Anna; Voci, Alberto; Valentini, Elisabetta; De Zaiacomo, Francesca; Catarini, Massimo; Iasevoli, Mario; Maggi, Stefania; Pegoraro, Renzo; Manzato, Enzo; Giantin, Valter
Abstract : Aim: The aim of the present study was to investigate the proportion of physicians and nurses who agree with the administration of antibiotic therapy (AT), artificial hydration (AH), and artificial nutrition (AN) in patients with advanced dementia and different life expectancies. Furthermore, we aimed at analyzing the correlates of the opinion according to which medical treatments should no longer be given to advanced dementia patients once their life expectancy falls. Methods: End‐of‐life decisions and opinions were measured with a questionnaire that was sent to geriatric units, hospices and nursing homes in three different regions of Italy. Multivariate logistic regressions were carried out to ascertain the correlates of the agreement with the administration of AH, AT or AN. Results: When the patient's life expectancy was 1–6 months, 83% of respondents agreed with AH, 79% with AT and 71% with AN. When the life expectancy was less than 1 month, a large proportion of respondents still agreed with AH and AT (73% and 61%), whereas less than one in two respondents (48%) agreed with AN. Conclusions: The findings of the present study showed that AN creates more ethical dilemmas in the clinical management of end of life than other treatments, such as AH or AT. Opinions on whether or not these practices are appropriate at the end of life were related with feelings, thoughts and ethical issues that played a different part for physicians and nurses.Geriatr Gerontol Int 2017; 17: 487–493.